2017
DOI: 10.1155/2017/7316354
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-2 Modulates the Survival, Differentiation, and Migration of Induced Pluripotent Cell-Derived Mesenchymal Stromal Cells

Abstract: Kindlin-2 is a multidomain intracellular protein that can be recruited to β-integrin domains to activate signaling, initiate transcriptional programs, and bind to E-cadherin. To explore its involvement in cell fate decisions in mesenchymal cells, we studied the effects of Kindlin-2 modification (overexpression/knockdown) in induced pluripotent cell-derived mesenchymal stromal cells (iPSC-MSCs). Kindlin-2 overexpression resulted in increased proliferation and reduced apoptosis of iPSC-MSCs, as well as inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Global deficiency of Kindlin-2 in mice caused early embryonic lethality, suggesting that Kindlin-2 plays a vital role in development 12 . Furthermore, recent reports have demonstrated that Kindlin-2 participates in numerous biological and pathological processes, such as cell apoptosis, differentiation, survival, and carcinogenesis 15 20 . Recently, Kindlin-2 was also reported to play an essential role in fibrotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Global deficiency of Kindlin-2 in mice caused early embryonic lethality, suggesting that Kindlin-2 plays a vital role in development 12 . Furthermore, recent reports have demonstrated that Kindlin-2 participates in numerous biological and pathological processes, such as cell apoptosis, differentiation, survival, and carcinogenesis 15 20 . Recently, Kindlin-2 was also reported to play an essential role in fibrotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Kindlin-2, a component of cell-extracellular matrix adhesions, activates integrin by binding with the cytoskeletal protein, talin and regulates cell adhesion, migration, proliferation, and differentiation (21). Recently, evidence has emerged that kindlin-2 holds great potential in wound healing and cell differentiation (17)(18)(19). The present study identified kindlin-2 as a key determinant of the differentiation of 3T3-L1 preadipocytes in wound healing and delineated the underlying signaling mechanism.…”
Section: Discussionmentioning
confidence: 62%
“…Wu et al and Guo et al demonstrated that depletion of kindlin-2 in MSCs inhibits cartilage formation, damages bone development, induces adipogenesis, and inhibits osteogenesis through controlling Yes-associated protein 1 (YAP1) and Taffazzin (TAZ) which are key signaling intermediates that link adhesive and mechanical cues to MSC differentiation (17,19). In iPSC-MSCs, overexpression of kindlin-2 leads to increased proliferation and decreased apoptosis, and inhibits their differentiation into osteocytes, adipocytes, and chondrocytes (18). Noticeably, we observed that kindlin-2 has the opposite effect of inducing adipogenesis and osteogenesis in 3T3-L1 preadipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kindlin-2 knockdown increased apoptosis and differentiation response whereas kindlin-2 overexpression increased proliferation, decreased apoptosis, and slowed down trilineage differentiation. More significantly, kindlin-2 overexpression increased the migration of iPSC-MSCs in the wound-scratch assay[ 130 ]. In the future, substantial efforts are needed to explore MSC stemness/potency-related regulators or biomarkers for clinical application.…”
Section: Discussionmentioning
confidence: 99%